PSICHOLOGY ENVIRONMENT DALAM PERENCANAAN RUMAH SAKIT JIWA DI KABUPATEN TOLITOLI - Rahayu, Sidri; Pahude, Mansur S.; Rosid, Mohammad (ANALOGI : Arsitektur, Lingkungan Binaan & Planologi, 2024)
In facing the increasing number of people with mental disorders in Indonesia, facilities are needed that support optimal services. Currently, Central Sulawesi Province is recorded as having 72,326 people with mental disorders in 2021 and the potential will continue to increase. The prevalence rate of more serious mental disorders, such as schizophrenia, is reported to be around 1.7 per 1000 population or around 400,000 people. This study aims to design a new mental hospital building by considering aspects of environmental psychology and human behavior. Mental hospitals have an important role in providing health and recovery services for individuals with mental disorders. Therefore, an architectural approach that pays attention to the relationship between space, humans, and the environment is essential in planning. The research method involves analyzing data from the Tolitoli Regency Health Office regarding the number of people with mental disorders from 2019 to 2021. The environmental and behavioral psychology architectural approach is used to design spaces that are in accordance with the characteristics of the patient's mental health. The use of the Systematic Literature Review (SLR) model in the architectural design of a mental hospital to systematically explore, analyze, and synthesize relevant literature as a reference in designing new buildings with the expected results in the form of a comprehensive picture of the best trends and approaches in architectural design. The results of this study are expected to contribute to the development of mental health facilities in Tolitoli Regency and be a consideration for the government and private sector in the construction of a Mental Hospital.